The Understanding of Islamic Teachings About Water and Environmental Care Attitudes and Their Relationships with Intentions to Save Water - Sri Purnami (Sekolah Tinggi Agama Islam Negeri (STAIN) Kudus, 2022)
Water is very important natural resources for our life so that it deserves to care. One of the global problem of water is its limited availability. Indonesia as a Moslem's country is known as wasteful in using water. Whilst, Islam teaches to care of water and not to use wastefully.  Moreover, since there are some natural disasters, people become more concern on environment. This research is aimed to study the correlation between the comprehension of Islamic teaching about water and environmental concern simultaneously with the intention to save water. Subject of this research is the students of Tarbiyah Faculty of Sunan Kalijaga Islamic University who are engaged in the 2nd series of PPL-KKN Integratif.  The data is obtained by employing the Intention to Save Water Scale, the Comprehension Test of Islamic Teaching about Water, and the Environmental Concern Scale. This research shows that 1) there is a positive and very significant correlation between  the comprehension of Islamic teaching about water and environmental concern simultaneously with the intention to save water (F=10.233, p<0.01); 2) there is no relationships between comprehension of Islamic teaching about water and intention to save water by controlling environmental concern variable ( rx1y,x1 = -.047, p>0.05) ; 3) there is a positive and very significant correlation between environmental concern and intention to save water by controlling  the comprehension of Islamic teaching about water variable (rx2y,x1 = 0.417, p<0.001).